Skin Store Information System Strategy Planning Mobile-Based Using the Ward And Peppard Method - Ariati, Nining; Akbar, Muhamad Hafiz; Melani, Afreti; Agustina, Geby Ayu; Aflah, Aulia Nur; Anjani (Acceleration, Quantum, Information Technology and Algorithm Journal, 2024)
The development of the beauty and self-care industry in Indonesia is accelerating, driving the need to digitize business processes to improve competitiveness. Cahaya Store, a beauty product store in Palembang, faces challenges such as the threat of new entrants, manual sales recording, and lack of digital platforms for online purchases. This research aims to design a mobile-based information system strategy using the Ward and Peppard method. The research stages involved internal and external environment analysis, SWOT, McFarlan Strategic Grid, value chain, and Porter's Five Forces. The results showed that the development of mobile e-commerce applications can provide online shopping accessibility, business process automation, and improved customer experience. The information system strategy includes the integration of inventory and sales management systems to improve operational efficiency and strengthen digital marketing. With the Ward and Peppard approach, Cahaya Store can formulate data-driven strategic steps to optimize information technology to support business growth and competitiveness. Research recommendations include the implementation of mobile applications with personalization features, customer relationship management, and continuous evaluation to maintain relevance to market dynamics.